TLR response pathways in NuLi-1 cells and primary human nasal epithelial cells. Issue 2 (December 2015) - Cooksley, Clare; Roscioli, Eugene; Wormald, Peter John; Vreugde, Sarah
Highlights: TLR 1-9 mRNA expression was conserved in NuLi-1 and HNECs. Several TLR related genes were differentially expressed in NuLi-1 cells vs HNECs. The two cell types showed a conserved response to TLR3 agonists. NuLi-1 cells did not exhibit differentiation at air-liquid interface. HNECs were more susceptible to infection by S. aureus than NuLi-1 cells. Abstract: The present study describes and compares functional properties of Nuli-1 cells and primary human nasal epithelial cells (HNEC) including TLR expression and function. Differences in gene expression were identified for non-TLR genes that play a role in TLR response pathways. However, experiments comparing TLR gene expression for both Nuli-1 cells and HNECs indicated conserved expression in both cell types. Stimulation of the two cell types resulted in a conserved response to TLR3 agonists, but in differences in response to agonists for TLR5 and TLR6/2. HNECs were much more susceptible to infection with Staphylococcus aureus than NuLi-1 cells. Furthermore, when cultured at air-liquid interface (ALI), NuLi-1 cells possessed much lower trans-epithelial resistance than primary HNEC and did not exhibit maintenance of cell morphology or mucous production which was observed in HNECs. Nor did they produce the characteristic interconnecting pattern of tight junction complexes at the apicolateral margin of adjacent cells. Caution should therefore be exercised when selecting cell lines for immunological studies and a thorough screen of properties relevant to the study should always be carried out prior to commencement.